Navidezna vseobsežnost načela non-refoulement - Šarić, Rok (Pravni letopis, 2023)
The principle of non-refoulement protects everyone from being returned to an environment in which their lives could be endangered and is an absolute right under international law. However, the practice of States and their courts has often shown a less than uniform understanding of the principle, which should certainly be interpreted as broadly as possible in the interests of protecting everyone‘s fundamental human rights and freedoms.
Keywords: begunci; človekove pravice; izgon; mednarodno pravo; načelo nevračanja; pravica do azila